Development of an ultrasonic integrated system to measure the mechanical propeties and acoustical characteristics of material - Mohamad Azrul Amat (N/A, 2016)
Development of an ultrasonic integrated system to measure the mechanical propeties and acoustical characteristics of material by Mohamad Azrul Amat